ELIMINATION OF WRITTEN SPEECH DEFICIENCES IN DISARTHRIC CHILDREN - Tajimuratova, K.A. (SCIENCE and SOCIETY, 2026)
The article examines the impact of dysarthria on children’s oral and written speech, its neurological causes, as well as written speech disorders such as dysgraphia and dyslexia. It also describes comprehensive speech therapy approaches to correcting written speech, including the development of phonemic perception, articulatory-breathing exercises, and graphomotor skill formation.
Keywords: dysarthria; motor speech disorder; cerebral palsy; neurological disorders; dysgraphia; dyslexia; phonemic perception; articulatory motor skills; prosody; speech breathing